2022
DOI: 10.1007/s10803-022-05792-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic Quarantine on Adults with Autism Spectrum Disorders and Intellectual Disability: A Longitudinal Study

Abstract: The impact of the pandemic is being very significant psychologically, especially for people who were already vulnerable in these aspects, such as adults with Autism Spectrum Disorders (ASD) and Intellectual Disability (ID). A longitudinal analysis of motor aspects such as balance and gait, executive functions in daily life, severity of symptoms characteristic of autism, and degree of subjective well-being was performed in 53 adults with ASD and ID. A repeated measures ANOVA was performed and three measures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The results obtained in this study show a correlation between aspects of social communication such as writing, leisure, and the emotional impact of the pandemic. This supports some of the previous results that had pointed to a worsening of the severity of the core symptoms of autism 5 . However, it has not been possible to demonstrate that these variables are protective nor that they explain the increase in the negative impact of the pandemic, so this causal relationship cannot be established.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results obtained in this study show a correlation between aspects of social communication such as writing, leisure, and the emotional impact of the pandemic. This supports some of the previous results that had pointed to a worsening of the severity of the core symptoms of autism 5 . However, it has not been possible to demonstrate that these variables are protective nor that they explain the increase in the negative impact of the pandemic, so this causal relationship cannot be established.…”
Section: Discussionsupporting
confidence: 92%
“…The consequences on mental health in the general population have been devastating, being more severe in those affected by a previous mental disorder, such as people with ASD 1 4 . In a previous study involving 53 adults who also participated in this research, this group was found to be particularly vulnerable, suffering deterioration in physical variables such as balance and severity of the core symptoms of the disorder 5 .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation